Determinants of Diabetic Complication Among Adult Diabetic Patients in Debre Markos Referral Hospital, Northwest Ethiopia, 2018: Unmatched Case Control Study - Kidanie BB (Dove Medical Press, 2020)
Bekalu Bewket Kidanie,1 Girma Alem,1 Haymanot Zeleke,1 Mihretie Gedfew,1 Afework Edemealem,2 Atsedemariam Andualem2 1Department of Nursing, College of Health Science, Debre Markos University, Debre Markos, Ethiopia; 2Department of Nursing, College of Health Science, Wollo University, Dessie, EthiopiaCorrespondence: Bekalu Bewket KidanieDepartment of Nursing, College of Health Science, Debre Markos University, Debre Markos, EthiopiaEmail bewket.bekalu2014@gmail.comBackground: Diabetes mellitus is a group of common metabolic disorders that share the phenotype of hyperglycemia, and are caused by a complex interaction of genetics and environmental factors. Diabetes mellitus produces change in the blood vessels and therefore affects almost every part of the body.Methods: A hospital-based unmatched case control study was conducted from February 2018 to April 2018 at Debre Markos Referral Hospital. Data were collected from 204 individuals, 136 controls and 68 cases using an interviewer-administered questionnaire and patient chart. Data were entered into EPI-data 3.1 software and exported to SPSS version 21 for analysis. Descriptive analysis including mean, median and proportions was carried out. In bivariate analysis, variables below 0.25 significance level were selected for multivariable analysis. For multivariable analysis, a backward model was selected and 95% confidence interval variables with P-values below 0.05 in multivariable analysis were declared as significant variables.Results: Of the total respondents, 68 were cases and 136 were controls, with an overall response rate of 98.55%. Of these respondents, 57.4% and 57.8% were males and type 1 diabetic patients, respectively. This study found that ages of 38– 47 (AOR= 5.60 (1.62– 19.38)) and > 47 (AOR=4.81 (1.32– 17.5)), income of 1000– 1499 (AOR=3.10 (1.05– 9.08)), self-reported drug adherence (AOR=5.146 (1.651– 16.04)), FBS of 70– 130 mg/dL 0.095 (0.022– 0.414) and ≥ 131 mg/dL (0.05 (0.011– 0.223)) and type 1 diabetic mellitus (AOR=4.73 (1.765– 12.72)) were significantly associated with diabetes mellitus complications.Conclusion and Recommendations: The study identified important determinants of diabetic complications. Poor glycemic control, poor adherence, and income were found to be modifiable determinants; on the other hand, age and type of diabetic mellitus are non-modifiable determinants of diabetic complications. Clinicians should implement a comprehensive care plan that will address patients’ adherence and glycemic control problems.Keywords: diabetic complication, glycaemic control, adherence